Karaim language in use - Firkavičiūtė, Karina; Statkienė, Natela; Rinkevičius , Šarūnas (Vilnius University Proceedings, 2024)
Karaim is a Turkic West Kipchak group language that reached Lithuania together with the Karaim community in the 14th century and ever since was preserved, used by the Karaims and still is spoken today exclusively in Lithuania by approximately 30 people. This volume offers an overview of the Karaim language’ state-of-the-art, its research, and reflects on it from its usage perspectives. Activities for the language retention by dedicated Karaim people are also presented here, as Karaims in Lithuania have always been very conscious about their native language and its challenges, and have greatly contributed to preserving the language for future generations. This publication summarises outcomes of the international scientific conference titled ‘Karaim language in use’ organised in 2022 by Lithuanian Karaim Association of Culture and The Institute of Asian and Transcultural Studies of Vilnius University (Lithuania) in partnership with the Jagiellonian University in Kraków (Poland) and the Embassy of the Republic of Poland. The conference made part of the programme celebrating 2022, the Year of the Karaims of Lithuania that was dedicated to commemorate the 625th anniversary of the establishment of the Karaim community in Lithuania.